Maternal Nodal inversely affects NODAL and STOX1 expression in the fetal placenta - Thulluru, Hari K.; Park, Craig; Dufort, Daniel; Kleiverda, Gunilla; Oudejans, Cees; Van Dijk, Marie (Frontiers in Genetics, 2013)
Nodal, a secreted signaling protein from the transforming growth factor beta (TGF-β)-super family plays a vital role during early embryonic development. Recently, it was found that maternal decidua-specific Nodal knockout mice show intrauterine growth restriction (IUGR) and preterm birth. The chromosomal location of NODAL is in the same linkage area as the placental (fetal) pre-eclampsia (PE) susceptibility gene STOX1, which is associated with the familial form of early-onset, IUGR-complicated PE. As the STOX1 linkage was originally identified in women being born from a pre-eclamptic pregnancy as well as suffering from PE themselves, the linkage could in part be caused by NODAL, which is why the potential maternal–fetal interaction between STOX1 and NODAL was investigated. In the PE families with the STOX1 susceptibility allele carried by the children born from pre-eclamptic pregnancies, it was found that the pre-eclamptic mothers themselves all carried the NODAL H165R SNP, which causes a 50% reduced activity. Surprisingly, in decidua-specific Nodal knockout mice the fetal placenta showed up-regulation of STOX1 and NODAL expression. Conditioned media of human first trimester decidua and a human endometrial stromal cell line (T-HESC) treated with siRNAs against NODAL or carrying the H165R SNP were also able to induce NODAL and STOX1 expression when added to SGHPL-5 first trimester extravillous trophoblast cells. Finally, a human TGF-β/BMP signaling pathway PCR-array on decidua and the T-HESC cell line with Nodal knockdown revealed upregulation of Activin-A, which was confirmed in conditioned media by ELISA. We show that maternal decidua Nodal knockdown gives upregulation of NODAL and STOX1 mRNA expression in fetal extravillous trophoblast cells, potentially via upregulation of Activin-A in the maternal decidua. As both Activin-A and Nodal have been implicated in PE, being increased in serum of pre-eclamptic women and upregulated in pre-eclamptic placentas respectively, this interaction at the maternal–fetal interface might play a substantial role in the development of PE.